A study on Ga – Si interdiffusion during (Al)GaN/AlN growth on Si by plasma assisted molecular beam epitaxy - Zheng, Y. (2020)
The Ga–Si interdiffusion during (Al)GaN/AlN growth on Si substrate by plasma assisted molecular beam epitaxy (PA-MBE) is studied. The epilayers were grown using a combination of different III/V ratios for GaN and AlN layers. The columnar morphology of the nitrogen-rich (III/V < 1) AlN nucleation layer allows the migration of Ga metal into Si, leading to the interdiffusion. The presence of less Ga at the GaN/AlN interface and the two-step growth process of AlN with different column sizes on the top and bottom AlN completely eliminates the possibility of Ga–Si interdiffusion. Alternatively, a thin silicon nitride as a nucleation layer for the growth of (Al) GaN layers was also found to prevent the Ga–Si interdiffusion thereby circumventing the process of melt-back etching.